2020
DOI: 10.1093/bib/bbaa359
|View full text |Cite
|
Sign up to set email alerts
|

A review on viral data sources and search systems for perspective mitigation of COVID-19

Abstract: With the outbreak of the COVID-19 disease, the research community is producing unprecedented efforts dedicated to better understand and mitigate the effects of the pandemic. In this context, we review the data integration efforts required for accessing and searching genome sequences and metadata of SARS-CoV2, the virus responsible for the COVID-19 disease, which have been deposited into the most important repositories of viral sequences. Organizations that were already present in the virus domain are now dedic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…Imaging data represent a particular subset of clinical data. A dated conceptual model for this information was proposed in [34] but more recent efforts are arising in the Cancer Genomics practice [35] and in the COVID-19 research community [36], as shown in [37].…”
Section: Data Typesmentioning
confidence: 99%
“…Imaging data represent a particular subset of clinical data. A dated conceptual model for this information was proposed in [34] but more recent efforts are arising in the Cancer Genomics practice [35] and in the COVID-19 research community [36], as shown in [37].…”
Section: Data Typesmentioning
confidence: 99%
“…2 In OntoUML models, we employ the generally-accepted color coding scheme: light red is used for types whose instances are objects, green when instances are relators, yellow when instances are events, and purple when instances are higher-order types. 3 By using the multi-modeling support in UFO/OntoUML, one could proceed further and explicitly capture the relations of subordination between, for example, species and genus, namely, that a type is subordinate to another iff the instances of the former are specializations of instances of the latter [9]. For space reasons, we do not elaborate further.…”
Section: Unpacking the Vcm In Ontoumlmentioning
confidence: 99%
“…The Viral Conceptual Model (VCM) [4] was motivated by interest in representing the genomic aspects of COVID-19 so they can be shared among the scientific and medical communities that are attempting to understand SARS-CoV-2 and similar pathogens. The model is being used for designing: an integrated data warehouse and search system [8]; a linked Phenotype Data Dictionary [3]; a knowledge base of variant impacts [1]; and a visualization engine [6]. To facilitate a further, robust, application of VCM to projects with other viruses and pathogens, there needs to be some way to assess the quality of the model.…”
Section: Introductionmentioning
confidence: 99%
“…New variants of SARS-Cov2 keep being described [55][56][57][58] and deposited in old, as well as new, dedicated sequence databases (reviewed in [59]). As a measure of the staggering numbers of sequences, GenBank, which is continuously updated from laboratories around the world, had about 300 SARS-CoV-2 nucleotide sequences by the end of March 2020, and 27 660 by October 8, 2020, an almost 100-fold increase in just 6 months.…”
Section: Sars-cov2 Variants the Future Challengementioning
confidence: 99%